Parametric Evaluation and Modeling of The Alignment Between TVET Matriculation Choices and University Program Enrollment - Ibrahim, Rosziati; Milala, Sani Inusa; Md Ariffin, Khadijah; Mat Rejab, Mazidah; Abdul Razzaq, Abdul Rasid; Jamel, Sapiee (Journal of Technical Education and Training, 2025)
Technical and Vocational Education and Training (TVET) plays a crucial role in equipping students with the skills necessary for industry-specific careers, yet there remains a gap in the alignment between TVET matriculation choices and subsequent university program enrollment. This misalignment may lead to challenges in students’ academic progression and career outcomes. The aim of this study is to critically assess the factors influencing the alignment between TVET students’ matriculation choices and their enrollment in university programs, with a focus on understanding students’ perceptions and experiences. The research adopts a quantitative approach, utilizing a survey method to collect data from a stratified random considering the population of 3500 population a sample of 347 polytechnic students from Malaysian Technical University Network (MTUN) institutions specifically UTHM, was dawn using krejcie and morgan table. The sample was divided into two batches to ensure representation across various stages of their academic programs. The primary data collection instrument was a structured questionnaire, which included Likert scale items to assess students’ views on assessment, curriculum implementation, and their alignment with industry requirements. Data were analyzed using descriptive and inferential statistical techniques, including t-tests and ANOVA. The findings reveal significant differences in student perceptions based on demographic and institutional factors, highlighting gaps in curriculum design and assessment practices. These findings suggest that misalignment between TVET programs and university curricula affects students’ academic and career outcomes. The study concludes that addressing these gaps through improved curriculum design, better assessment practices, and stronger industry linkages is essential for enhancing the effectiveness of TVET education and supporting sustainable student success in the workforce.